2006
DOI: 10.1063/1.2345375
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light emission from one-layered organic light-emitting devices doped with organic salt by simultaneous thermal and electrical annealing

Abstract: The authors studied the effect of thermal and electrical annealing on light emission of fluorescent one-layered organic light-emitting devices (OLEDs) doped with organic salts. From the annealed OLEDs, we clearly observed homogeneous and enhanced electroluminescent (EL) emission over the whole active area with fast responses. Moreover, improved efficiency was also observed from annealed phosphorescent OLEDs. These improved EL characteristics indicate that simultaneous annealing can induce proper adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…1-9 Major important technological issues regarding high-performance OLED displays pertain to device efficiency, stability, and ease of fabrication. 10,11 Although such efficient wet-processed PHOLEDs have been demonstrated, the processes of their fabrication remain inadequate; the device structure is still complex because a hole injecting layer of poly͑3,4-ethylenedioxythiophene͒:poly͑4-styrenesulphonate͒ ͑PE-DOT:PSS͒ has usually been introduced between the emissive layer and the transparent indium-tin-oxide ͑ITO͒ anode. [3][4][5][6] By contrast, insufficient progress has been made in achieving strong light emission from a simple OLED structure.…”
Section: Solution Processable Ionic P-i-n Phosphorescent Organic Lighmentioning
confidence: 99%
“…1-9 Major important technological issues regarding high-performance OLED displays pertain to device efficiency, stability, and ease of fabrication. 10,11 Although such efficient wet-processed PHOLEDs have been demonstrated, the processes of their fabrication remain inadequate; the device structure is still complex because a hole injecting layer of poly͑3,4-ethylenedioxythiophene͒:poly͑4-styrenesulphonate͒ ͑PE-DOT:PSS͒ has usually been introduced between the emissive layer and the transparent indium-tin-oxide ͑ITO͒ anode. [3][4][5][6] By contrast, insufficient progress has been made in achieving strong light emission from a simple OLED structure.…”
Section: Solution Processable Ionic P-i-n Phosphorescent Organic Lighmentioning
confidence: 99%
“…These often occur under a high-electric field inside an OLED, but not under photoexcitation. Besides, it has been shown that EL spectra of OLED did not significantly change by doping with organic salt [9,10,13,14]. The PL spectrum of TBAPF 6 doped-films showed peak near 425 nm, which can be attributed to the PVK:PBD exciplex emission [32].…”
Section: Resultsmentioning
confidence: 94%
“…The start up of current in the first voltage scan could be attributed to the predominant contribution of ionic current. This is expected as due to the polarization of ions in organic layer to build up ions alignment near the electrodes [9][10][11][12][13][14]. The applied voltage at which the current density increased drastically is assigned as transition voltage in this paper.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This device is simple, and hence potentially inexpensive to make. However, there still remain problems regarding inhomogeneous emission, low reproducibility, and undesirable electric field treatment at high field strength over 20 V. Thus, the effect of doping with salt on performance in OLEDs has not yet been fully investigated (Yim et al, 2006). Hence, a new work was initiated to improve the device's high efficiency and brightness further by doping with organic salt and simultaneous treatments of electrical and thermal annealing.…”
Section: Introductionmentioning
confidence: 99%